Rancang Bangun Pengemasan Produk Kacang Goreng Otomatis Berbasis Mikrokontroler - Yusni Hasanah; Nefy Puteri Novani (CHIPSET)
The working system of this Automatic Fried Bean Product Packaging tool uses Arduino Mega2560 as a microcontroller, then a screw on the funnel to accelerate  the descent of the product into the packaging plastic and prevent blockages, infrared sensors to detect product availability in storage containers. The tool made uses volume measurements to minimize error on the scales using a load cell sensors. The type of research used in making the final assignment is action research which is carried out carefully, logically and systematically. The conclusions of this research are (1) The system can detect the supply of fried peanuts in the funnel/silo using  infrared FC-51 sensor with a distance range of 1 – 8 cm. (2) The system can read the mass input selected by user, namely 75 g, 100 g, and 150 g with a push button and displayed through the LCD. (3) The system can fill the fried peanuts into packages according to the mass that has been set through the KY-008 laser sensor and laser receiver, using the tube volume formula  with a percentage error of 4.5% for a mass of 75 grams, 3.83% for a mass of 100 grams, and 5.41% for a mass of 150 grams. (4) The system can perform the package closing process using servo motors, heating elements, and stepper motors. The duration of time required by the heating element in gluing the plastic ranges from 3 to 4 seconds.